PENGARUH SOCIAL SUPPORT DAN SELF-ESTEEM TERHADAP OPTIMISME FRESHGRADUATE S-1 YANG SEDANG MENCARI KERJA - Laela Kamila; Marhisar Simatupang; Holy Greata Singadimedja (Psikologi Prima, 2023)
A This study aims to determine the effect of social support and self-esteem on the optimism of bachelor degree freshgraduates who are looking job in Karawang. In this study there are three variables, namely social support, self-esteem and optimism. The major hypothesis in this study is that there is an influence of social support and self-esteem on the optimism of bachelor degree freshgraduates who are looking job in Karawang. The number of samples used was 116 freshgraduated bachelor degree freshgraduates who are currently looking job in Karawang. The sampling method in this study used Snowball sampling and the data analysis technique used was multiple linear regression with SPSS 25.0. Based on the results of hypothesis testing it is known that social support and self-esteem variables have an influence with a significance value of 0.000 <0.05. The results showed there is the influence of social support and self-esteem together at 0.232 or 23.2% contributed to the optimism of bachelor degree freshgraduates who were looking job in Karawang while the rest were influenced by other factors outside of this study.